Climbing the Ivory Tower: How Socio-Economic Background Shapes Academia - Ran Abramitzky; Lena Greska; Santiago Pérez; Joseph Price; Carlo Schwarz; Fabian Waldinger (CESifo GmbH, 2024)
We explore how socio-economic background shapes academia, collecting the largest dataset of U.S. academics' backgrounds and research output. Individuals from poorer backgrounds have been severely underrepresented for seven decades, especially in humanities and elite universities. Father's occupation predicts professors' discipline choice and, thus, the direction of research. While we find no differences in the average number of publications, academics from poorer backgrounds are both more likely to not publish and to have outstanding publication records. Academics from poorer backgrounds introduce more novel scientific concepts, but are less likely to receive recognition, as measured by citations, Nobel Prize nominations, and awards.
Keywords: 330; academics; socio-economic background; science; U.S. census